Pengaruh Jam Posting terhadap Engagement Rate - Ghefira Sari Kholili; Yanti Susanti (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2026)
This study aims to analyze the effect of posting time on engagement rates on social media. Engagement rate is a crucial indicator for measuring the success of content, encompassing interactions such as likes, comments, shares, and other responses. Using data on posting time and audience interaction levels, this study demonstrates significant differences in engagement rates based on content publication time. Content posted during audience-active hours generates higher engagement rates than content published during off-peak hours. These findings underscore the importance of a content scheduling strategy as part of social media management to maximize the reach and effectiveness of digital communications. This research also provides practical implications for businesses, content creators, and social media managers in determining optimal times to enhance content performance organically. It can also be used to develop more targeted scheduling techniques based on relevant audience data and habits. It is recommended that the use of analytics tools that can monitor audience active times further strengthen social media management strategies.